2022
DOI: 10.3390/su14042194
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Dimension of Land–Sea Interactions in Maritime Spatial Planning: Three Case Studies in the Baltic Sea Region

Abstract: Spatial planning faces challenges in addressing interactions between land and sea. This paper elaborates on land–sea interfaces, which can integrate certain socio-cultural values and related tensions into maritime spatial planning (MSP). In this article, three regional case studies from Estonia, Latvia, and Poland analysed important intersections between the formations of cultural values and spatial dynamics within MSP processes. These cases make it possible to address current challenges, contested boundaries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…The inland part of the study area is used for agriculture, forestry, and, more recently, wind energy production. Currently, wind turbines are operational in the onshore part, but there is an emerging interest among developers in building offshore wind farms in the adjacent territorial waters and Exclusive Economic Zone [26]. Key maritime economic activities in the study area include coastal tourism, fishing, and shipping [41].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The inland part of the study area is used for agriculture, forestry, and, more recently, wind energy production. Currently, wind turbines are operational in the onshore part, but there is an emerging interest among developers in building offshore wind farms in the adjacent territorial waters and Exclusive Economic Zone [26]. Key maritime economic activities in the study area include coastal tourism, fishing, and shipping [41].…”
Section: Study Areamentioning
confidence: 99%
“…A similar approach was applied by Inácio et al [72] in mapping and assessing coastal CES in a neighboring country-Lithuania, where various spatial data sets were used to model the natural components (e.g., naturalness, relief heterogeneity, tree density, water bodies, and other landcover types, silent areas, protected areas) and cultural components (e.g., religious sites, points of interest, sports facilities, accommodation, gastronomy, tourism infrastructure) contributing to CES supply; whereas flow and demand of the services were assessed using the online PGIS survey, identify the sites visited for recreation and points of origin of respondents as well as using this information also for verification of the supply assessment. Our approach differs in terms of the assess-ment unit-landscape area, which encompasses relatively homogeneous biophysical and socio-cultural characteristics as well as place identity [26], therefore being more recognizable/perceivable by local stakeholders and robust for decision-making. The applicability of landscape areas in decision-making and conveying planning solutions was highlighted by Hazeau et al [48] and Fish et al [73] and demonstrated in our study by using the CES assessment at the scale of landscape areas to guide the costal tourism development recommendations and their communication to stakeholders.…”
Section: Integrated Approach In Ces Assessment To Support Coastal Pla...mentioning
confidence: 99%
See 1 more Smart Citation
“…2022). Dodatkowo sztywny podział administracyjny i podział kompetencji na linii morze-ląd w warunkach polskich utrudnia, a często wręcz uniemożliwia, zarządzanie usługami ekosystemowymi na styku tych dwóch środowisk(Pikner i in. 2022).…”
unclassified
“…According to many sources, the Caribbean has been the dominant market for cruises since its inception. The Caribbean and the Mediterranean are regional and complementary markets, accounting for more than 70% of the world's cruise industry capacity, offering a variety of cultures in close proximity and therefore a perfect match [13]. These markets are complementary in the sense that the Caribbean is mainly served in the winter, while the Mediterranean peaks in the summer.…”
mentioning
confidence: 99%